Optimality Theoretic Analysis of Non-Rhoticity in English - Ostalski, Przemysław (Research in Language, 2007)
The paper intends to describe various rhotic phenomena within a unified phonological framework of Optimality Theory. This description encompasses “standard” rhotic phenomena, such as linking and intrusive r. Additionally both hyper- and hypo-rhoticity are discussed. The paper serves primarily two points. First, it proves practical workability of constraint mechanism, as proposed by Optimality Theory. Second, it presents an integrated account of seemingly unrelated phonological facts observed in various accents of English. The paper discusses also previous accounts of rhoticity in English in connection with an attempt of presenting solid evidence for the choice of underlying forms. Furthermore two competing theoretical descriptions of rhotic insertions (epenthesis vs. gliding/spreading) are compared and evaluated. Finally, the spreading account is shown to be formally superior to the anti-hiatus approach. Moreover, the paper demonstrates a way in which r-liaison might be incorporated in the synchronic grammar of non-rhotic accents. Simply put, r-liaison could be perceived as another instantiation of VSPREAD conspiracy, where vowels tend to spread their melodic content onto the following segments. The OT machinery was also employed to account for the differences between various subtypes of non-rhotic accents, in terms of re-ranking of several constraints. The peculiar phenomena of hyper-rhoticity have, too, been demonstrated to fit the proposal.